2020
DOI: 10.1111/jonm.13018
|View full text |Cite
|
Sign up to set email alerts
|

General phenomenon and communication experience of physician and nurse in night shift communication: A qualitative study

Abstract: CorrespondenceFengying Kang, Resident standardized training central, The First Abstract Aim: This paper explored the general phenomenon and psychological experience of the special background communication in night shift medical staff and provides better reference for night shift communication between doctors and nurses.Background: Physician-nurse communication has always been an important agenda for health care work and an important concept in nursing theory. During night shifts, effective doctor and nurse com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…On the contrary, the results of the study of Gabriele Prati (2014) show that physicians have a better understanding of the significance of teamwork and claim to be more involved in teamwork activities [ 27 ]. It appears that the main reasons for the personnel’s greater emphasis on teamwork are differences between individuals’ professional perceptions and physician-centeredness in Iran: from the physicians’ point of view, since operations are performed by surgeons, teamwork in the operating room means being aware of the surgeons’ needs and following the surgeons’ instructions, not consulting others or transferring experiences [ 1 , 28 ]. In addition, since the healthcare system in Iran belongs to the public sector and the hospitals in the present study were educational organizations, the surgeons in these hospitals are frequently replaced by other surgeons, while the other personnel’s stay lasts for many years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the results of the study of Gabriele Prati (2014) show that physicians have a better understanding of the significance of teamwork and claim to be more involved in teamwork activities [ 27 ]. It appears that the main reasons for the personnel’s greater emphasis on teamwork are differences between individuals’ professional perceptions and physician-centeredness in Iran: from the physicians’ point of view, since operations are performed by surgeons, teamwork in the operating room means being aware of the surgeons’ needs and following the surgeons’ instructions, not consulting others or transferring experiences [ 1 , 28 ]. In addition, since the healthcare system in Iran belongs to the public sector and the hospitals in the present study were educational organizations, the surgeons in these hospitals are frequently replaced by other surgeons, while the other personnel’s stay lasts for many years.…”
Section: Discussionmentioning
confidence: 99%
“…Proper professional communication is characterized by “showing respect for professional values and personal abilities, relying on one’s colleagues’ knowledge and experience, and seeking advice before making decisions.” Establishment of proper professional communication in hospitals has always been a challenge in providing quality care to patients [ 1 ]. To reach their common goal, i.e., restoring their patients to good health within a certain period, the members of healthcare teams (physicians and nurses) need to observe the principles of professional communications, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 33 studies (34 reports, as one study was reported across two articles) were reviewed for methodological quality and were of moderate to high quality: Four articles38-41 met all 10 of the critical appraisal criteria, six articles42-47 met nine of the criteria, nine articles48-56 met eight of the criteria, 13 articles57-68,70 met seven of the criteria, one article71 met six of the criteria, and one article69 met five of the criteria. All studies rated positively for questions related to congruity between research methodology and research question (Q2), research methodology and methods (Q3), research methodology and representation of the analysis of data (Q4), and voices represented (Q8).…”
Section: Resultsmentioning
confidence: 99%
“…All used a qualitative methodology; specifically, 19 used qualitative descriptive,39-41,44,46,48-50,53,54,57,59-62,66,69-71 10 were phenomenology,38,42,43,45,47,52,55,56,58,63 two were ethnography,51,65 one was narrative,64 one was participatory action research,67 and one was mixed methods inclusive of a qualitative component, which allowed extraction of data relevant to this review 68. Studies used semi-structured in-person or telephone interviews,38-42,44,46,49-51,54-60,63-66,69-71 interviews with open-ended question,45,47,53 focus groups and interviews,43,62 focus groups,48,61,67 open-ended survey questions with electronic or pen and paper responses,68 and written statements 52. For one paper that used a semi-structured interview,64 data findings were extracted from the published paper while illustrations were extracted from supplementary data provided by the authors 72.…”
Section: Resultsmentioning
confidence: 99%
“…Some effects may be similar to other vocational activities after short or long periods of sleep deprivation 11 . The tasks routinely performed by healthcare staff are not only related to themselves but also may affect the health status of patients 12–14 . Any delayed or decreased cognitive and psychomotor capabilities of emergency medicine specialists could potentially be dangerous in patient management and lead to an increase in preventable errors 15 …”
Section: Introductionmentioning
confidence: 99%